Unterstützung von Verstehen im Fachunterricht. Eine Grounded Theory zum sprach- und fachverbindenden Geschichtsunterricht - Müller, Jennifer
Wie verläuft der Leseprozess im Geschichtsunterricht für Schüler:innen, die neu in das deutsche Bildungssystem einsteigen – und welche Faktoren beeinflussen ihr Verstehen? Diese Studie untersucht an der Schnittstelle von Deutsch als Zweitsprache und Geschichtsdidaktik die Bedingungen des Lesens im Geschichtsunterricht. Im Fokus stehen die Erfahrungen von Seiteneinsteiger:innen sowie die Perspektiven der Lehrkräfte, die im Rahmen einer qualitativ‑explorativen Untersuchung mithilfe von Unterrichtshospitationen, Interviews und Materialanalysen erhoben wurden. Methodisch ist die Arbeit in der Grounded Theory Methodology nach Strauss und Corbin (1996) verankert, anhand derer die komplexen Einflussfaktoren historischer Leseprozesse systematisch herausgearbeitet werden. Die Ergebnisse zeigen drei zentrale Einflussdimensionen: sprachliche, sozial‑affektive und geschichtsspezifische Faktoren. Zudem wird deutlich, dass Unterstützungsmaßnahmen stets zwischen kurzfristiger Hilfe und dem langfristigen Aufbau von Disciplinary Literacy ausbalanciert werden müssen. Ihre Wirksamkeit hängt wesentlich von der bewussten Auswahl und Zugänglichkeit durch die Lehrkraft sowie von den Möglichkeiten der Lernenden ab, Unterstützung gezielt einzufordern. Lernwirksam wird Geschichtsunterricht besonders dann, wenn hohe fachliche Anforderungen mit reflektierter sprachlicher Unterstützung verbunden werden. Die Studie leistet damit einen Beitrag zur Forschung zu sprachbewusstem Fachunterricht und bietet Impulse für eine kritisch‑reflexive Sprachsensibilität in schulischen Bildungsprozessen.
Keywords: Scaffolding; Sprache und Fach; Grounded Theory Methodology; Lesen in der Sekundarstufe I; Sprachsensibler Geschichtsunterricht; Durchgängige Sprachbildung

Transferability as a key to impactful entrepreneurship education outcomes: a new quest - Winkler, Christoph; Jenert, Tobias; Fust, Alexander (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Methodology; Entrepreneurship Education; Entrepreneurship Research

Open Science - Steinhardt, Isabel; Röwert, Ronny (Hochschulforschung)
In diesem Beitrag wird zunächst die historische Entstehung von Open Science kurz skizziert und definiert, was unter diesem Begriff zu verstehen ist. Daran anschließend werden die Open-Science-Praktiken Open Data, Open Access, Open Source, Open Methodology und Open Peer Review dargestellt und diskutiert, welche Forschungserkenntnisse zu Open Science vorhanden sind. Im Schluss werden Forschungsdesiderate aufgegriffen und die Implikationen von Open Science für die Wissenschaft erläutert.
Keywords: Open Data; Open Access; Open Source; Open Methodology; Open Peer Review

Women Philosophers from the Renaissance to the Enlightenment
This collection of essays presents new work on women’s contribution to philosophy between the Renaissance and the mid-eighteenth century. They bring a new perspective to the history of philosophy, by highlighting women’s contributions to philosophy and testifying to the rich history of women’s thought in this period. By showing that women were active in many branches of philosophy (metaphysics, science, political philosophy cosmology, ontology, epistemology) the book testifies to the rich history of women’s thought across Europe in this period. The scope of the collection is international, both in terms of the philosophers represented and the contributors themselves from Britain and North America, but also from continental Europe and from as far afield as Australia and Brazil. The philosophers discussed here include both figures who have recently come to be better known (Elisabeth of Bohemia, Anne Conway, Mary Astell, Catharine Trotter Cockburn, Emilie du Châtelet), and less familiar figures (Moderata Fonte, Lucrezia Marinella Arcangela Tarabotti, Tullia d’Aragona, Madame Deshoulières, Madame de Sablé, Angélique de Saint-Jean Arnauld d’Andilly, Olivia Sabuco, Susanna Newcome). The chapters in this book were originally published as a special issue of the British Journal for the History of Philosophy.
Keywords: History of Women Philosophers; Methodology; History of Philosophy; Women's Studies; Gender History

Distinguishing Knowledge Impact from Citation Impact: A Methodology for Analysing Knowledge Impact for the Literature Review Genre - Schryen, Guido; Wagner, Gerit; Benlian, Alexander
The scientific impact of research papers is multi-dimensional and can be determined quantitatively by means of citation analysis and qualitatively by means of content analysis. Accounting for the widely acknowledged limitations of pure citation analysis, we adopt a knowledge-based perspective on scientific impact to develop a methodology for content-based citation analysis which allows determining how papers have enabled knowledge development in subsequent research (knowledge impact). As knowledge development differs between research genres, we develop a new knowledgebased citation analysis methodology for the genre of standalone literature reviews (LRs). We apply the suggested methodology to the IS business value domain by manually coding 22 LRs and 1,228 citing papers (CPs) and show that the results challenge the assumption that citations indicate knowledge impact. We derive implications for distinguishing knowledge impact from citation impact in the LR genre. Finally, we develop recommendations for authors of LRs, scientific evaluation committees and editorial boards of journals how to apply and benefit from the suggested methodology, and we discuss its efficiency and automatization.
Keywords: Scientific impact; knowledge impact; content-based citation analysis; methodology

Designing a Novel Strategy for Exploring Literature Corpora - Wagner, Gerit; Empl, Philipp; Schryen, Guido (28th European Conference on Information Systems (ECIS 2020))
Understanding a new literature corpus can be a grueling experience for junior scholars. Nevertheless, corresponding guidelines have not been updated for decades. We contend that the traditional strategy of skimming all papers and reading selected papers afterwards needs to be revised. Therefore, we design a new strategy that guides the overall exploratory process by prioritizing influential papers for initial reading, followed by skimming the remaining papers. Consistent with schemata theory, starting with in-depth reading allows readers to acquire more substantial prior content schemata, which are representa-tive for the literature corpus and useful in the following skimming process. To this end, we develop a prototype that identifies the influential papers from a set of PDFs, which is illustrated in a case study in the IT business value domain. With the new strategy, we envision a more efficient process of exploring unknown literature corpora.
Keywords: Reading and skimming; Exploring literature; Review methodology; Design science research; Schemata theory

Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields? - Schryen, Guido; Benlian, Alexander; Rowe, Frantz; Shirley, Gregor; Larsen, Kai; Petter, Stacie; Paré, Guy; Wagner, Gerit; Haag, Steffi; Yasasin, Emrah (Communications of the AIS)
Literature reviews (LRs) are recognized for their increasing impact in the information systems literature. Methodologists have drawn attention to the question of how we can leverage the value of LRs to preserve and generate knowledge. The panelists who participated in the discussion of ?Standalone Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields?? at ICIS 2016 in Dublin acknowledged this significant issue and debated a) what the IS field can learn from other fields and where IS-specific challenges occur, b) how the IS field should move forward to foster the genre of LRs, and c) what best practices are to train doctoral IS students in publishing LRs. This article reports the key takeaways of this panel discussion. Guidance for IS scholars is provided on how to conduct LRs that contribute to the cumulative knowledge development within and across the IS field to best prepare the next generation of IS scholars.
Keywords: Literature Review; Review Methodology; Research Methodology; Doctoral Training

Utilizing big data analytics for information systems research: Challenges, promises and guidelines - Müller, Oliver; Junglas, Iris; vom Brocke, Jan; Debortoli, Stefan (European Journal of Information Systems)
Keywords: analytics; big data; data source; information systems research; methodology

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

An Analysis of Literature Reviews on IS Business Value: How Deficiencies in Methodology and Theory Use Resulted in Limited Effectiveness - Schryen, Guido (Proceedings of the First Scandinavian Conference on Information Systems (SCIS))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. This paper assumes that literature reviews, which represent a powerful instrument for the identification and synthesis of knowledge, have not tapped their full potential to address this issue due to deficiencies in methodology. The analysis of 18 literature reviews published in pertinent academic outlets during the past 20 years shows such deficiencies. Two of the most critical weaknesses identified are (1) the lack of theory use in most reviews and (2) a weak linkage of reviews, resulting in little progress in theory and framework development. The systematic identification of these weaknesses and the extraction of promising methodological examples from past literature are the main contributions of this work, which supports the composition of more effective literature reviews in future research.
Keywords: Literature review; Business value; Information systems; Methodology; Theory

Formal Refinement and Model Checking of An Echo Cancellation Unit - Krupp, Alexander; Müller, Wolfgang; Oliver, Ian (Proceedings of DATE’04 Designers' Forum)
This article presents an approach, which combines theorem proving-based refinement with model checking for state based real-time systems. Our verification flow starts from UML state diagrams, which are translated to the formal B language and are model checked for real-time properties. By means of the B language and a B theorem prover, refined state diagrams are verified against their abstract representation. The approach is presented by means of the refinement of a digital echo cancellation unit.
Keywords: Echo cancellers; Logic; Unified modeling language; Automata; Data structures; Boolean functions; Electronic design automation and methodology; Prototypes; Specification languages; Constraint theory

The Simulation Semantics of SystemC - Müller, Wolfgang; Ruf, Jürgen; Hoffmann, D. W.; Gerlach, Joachim; Kropf, Thomas; Rosenstiehl, W. (Proceedings of the Design, Automation, and Test in Europe (DATE’01))
We present a rigorous but transparent semantics definition of SystemC that covers method, thread, and clocked thread behavior as well as their interaction with the simulation kernel process. The semantics includes watching statements, signal assignment, and wait statements as they are introduced in SystemC V1.O. We present our definition in form of distributed Abstract State Machines (ASMs) rules reflecting the view given in the SystemC User's Manual and the reference implementation. We mainly see our formal semantics as a concise, unambiguous, high-level specification for SystemC-based implementations and for standardization. Additionally, it can be used as a sound basis to investigate SystemC interoperability with Verilog and VHDL.
Keywords: Yarn; Formal verification; Kernel; Hardware design languages; Electronic design automation and methodology; Algebra; Computational modeling; Logic functions; Computer languages; Clocks